2013
DOI: 10.1037/a0031051
|View full text |Cite
|
Sign up to set email alerts
|

Housing assistance and case management: Improving access to substance use disorder treatment for homeless veterans.

Abstract: The problem of waiting list attrition in addiction treatment programs is widespread, and homeless and marginally housed individuals are particularly susceptible. This naturalistic, retrospective study describes an intervention (Transitional Supportive Housing and Case Management) that effectively promoted treatment admission for this high-risk group above and beyond that which could be explained by certain pretreatment factors. The clinical records of 211 military veterans referred to intensive outpatient addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Case management has consistently shown to improve M a n u s c r i p t myriad outcomes for homeless youth (Ferguson, 2007;Kushel et al, 2006;McGrew & Danner, 2009;Slesnick et al, 2008;Winn et al, 2013), and while homeless youth have been shown to be avid users of technology (Guadagno et al, 2012;Pollio et al, 2013;, very few research efforts have sought to investigate the prospects of conjoining homeless youths' prolific technology use along with the potential effectiveness of delivering case management services from mobile, or "electronic" approaches. While many youth engaged in electronic case management, some required frequent attempts at contact before responding, suggesting the importance of case manager persistence, positive rapport-development with the youth over time, and commitment on the part of the youth to stay in touch with the case manager.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Case management has consistently shown to improve M a n u s c r i p t myriad outcomes for homeless youth (Ferguson, 2007;Kushel et al, 2006;McGrew & Danner, 2009;Slesnick et al, 2008;Winn et al, 2013), and while homeless youth have been shown to be avid users of technology (Guadagno et al, 2012;Pollio et al, 2013;, very few research efforts have sought to investigate the prospects of conjoining homeless youths' prolific technology use along with the potential effectiveness of delivering case management services from mobile, or "electronic" approaches. While many youth engaged in electronic case management, some required frequent attempts at contact before responding, suggesting the importance of case manager persistence, positive rapport-development with the youth over time, and commitment on the part of the youth to stay in touch with the case manager.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, case management has been shown to improve homeless youths' social adjustment in a variety of ways. Among homeless adults, engaging in case management services is additionally associated with an increased adherence to HIV treatment (Kushel et al, 2006), as well as an increased likelihood of enrolling and engaging in outpatient addiction treatment (Winn et al, 2013).…”
mentioning
confidence: 99%
“…Rapp, 2006;Vanderplasschen, Rapp, Wolf, & Broekaert, 2007). Over the many years in which the impact of case management in substance abuse treatment has been assessed, the positive contribution of this service to engagement and retention remains the most robust finding to date (Kim et al, 2011;Krupski, Campbell Rapp et al, 2014;Sosin & Durkin, 2007;Vanderplasschen et al, 2004Vanderplasschen et al, , 2007Winn et al, 2013). In a recent meta-analysis, R. Rapp and associates (2014) noted the impact of case management on treatment tasks, in particular activities that link clients to a range of needed services, as well as treatment retention.…”
Section: The Impact Of Case Managementmentioning
confidence: 93%
“…To list a few, case management has been useful with clients in detoxification services (Kirk et al, 2013), veterans (Winn et al, 2013), women in the public welfare system (Morgenstern et al, 2009), homeless individuals (Sosin & Durkin, 2007), clients in methadone maintenance programs (Coviello, Zanis, Wesnoski, & Alterman, 2006), and adolescents (Noel, 2006).…”
Section: The Impact Of Case Managementmentioning
confidence: 99%
“…Housing assistance, case management, regular phone contact, motivational interviewing and parental involvement for youth cases all decrease waiting list attrition. 2,20,21 In contrast, research also suggests that too many demands or requirements of patients during the waiting period is a deterrent for waiting. 8 In a pre-treatment survey, 16% of patients indicated that "I will have to go through too many steps to get into treatment" was a large barrier to entering treatment, along with the fact that they would have to be on a waiting list in the first place (34.3%).…”
Section: Why Patience Is Not Enoughmentioning
confidence: 98%